Workshop Kajian Fiqih Kewanitaan Guna meningkatkan Pemahaman tentang Haid Dan Istihadhah Menurut Syariat Islam - Nasrulloh, Muhammad Farid; Fodhil, Muhammad; Taufiq, Muhammad Irvan; Shobirin, Mochammad Syafiuddin; Wafa, Muhammad Aliyul (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Women are like pearls that are protected and jewels that are kept, because Islam guarantees the Shari'a, and Islamic deeds are in accordance with the character and characteristics of women, as long as they do not violate the texts of the Al-Qur'an or the Sunnah of the Prophet and the guidance of the Shari'a. Partners in this community service activity are Karang Taruna and IPPNU Betek Village. Based on the results of the situation analysis above, problems arise that need to be resolved regarding the planned community service activities in this Community Partnership Program scheme for partners, namely (1) There is still a lack of understanding among young women regarding women's jurisprudence which discusses menstruation and istihadhah. (2) There is still a lack of understanding about calculating menstrual time and istihadhah. Community service activities through seminars on women's jurisprudence which discuss menstruation and istihadhah among young women at Karang Taruna and IPPNU Betek Village have the objectives, namely (1) To improve and develop religious learning about women's jurisprudence. (2) To increase understanding of calculating menstrual time and istihadhah. This community service activity can be concluded that there is a lack of understanding in the community about menstruation and istihadzah correctly according to Islamic law, in this case KARTA and IPPNU lack understanding about menstruation and istihadzah, which then became the basis for holding seminar training on menstruation and istihadzah in Betek Village, Then, after conducting this study, we received positive responses and results. This can be proven by the average response to the questionnaire which reached 71.43%.